Recycling for death: coffin reuse in Ancient Egypt and the Theban Royal Caches - Cooney, Kara (American University in Cairo Press, 2024)
Intro -- Front Matter_CROP MARKS.pdf -- Chapter 1_CROP MARKS.pdf -- Chapter 2_CROP MARKS.pdf -- Chapter 3_CROP MARKS.pdf -- Chapter 4_CROP MARKS.pdf -- Chapter 5_CROP MARKS.pdf -- Chapter 6_CROP MARKS.pdf -- Chapter 7_CROP MARKS.pdf -- BIB_CROP MARKS.pdf -- Index_CROP MARKS.pdf.